Syvolapenko T.L. Analysis of current status of organizational and legal mechanism for strategic management in service-oriented state - Gryshyna, Nataliia (Pressing Problems of Public Administration, 2019)
The analysis of the model dimensions for a service-oriented state has been carried out. The peculiarities of strategies in the current process of public administration reform are identi ed.The essence of the service logic of the state institutions, their purpose and activities are generalized. The necessary condition for the functioning and development of strategic public administration isde ned as the subject orientation of its activity. The main problems of implementing the theory of a ’service’ state in Ukraine and ways to solve them are determined.